Two mechanisms drive pronuclear migration in mouse zygotes - Kathleen Scheffler (Nature Portfolio, 2021)
In a newly fertilized egg, maternal and paternal chromosomes are enclosed in two separate pronuclei but the mechanisms in mammals for pronuclear movement are unclear. Here, the authors report that both F-actin and microtubule polymerization act in concern to drive inward movement of pronuclei towards the cell centre.